Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1007/11753728_60
|View full text |Cite
|
Sign up to set email alerts
|

Extended Resolution Proofs for Conjoining BDDs

Abstract: Abstract. We present a method to convert the construction of binary decision diagrams (BDDs) into extended resolution proofs. Besides in proof checking, proofs are fundamental to many applications and our results allow the use of BDDs instead-or in combination with-established proof generation techniques, based for instance on clause learning. We have implemented a proof generator for propositional logic formulae in conjunctive normal form, called EBDDRES. We present details of our implementation and also repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 36 publications
2
66
0
Order By: Relevance
“…Recently, there has been a lot of interest in the relative efficiency of satisfiability checking methods based on resolution and OBDDs [1,2,3,4,5,6]. While OBBDs in general are known to be in cases exponentially more efficient that unrestricted resolution [7], it has been recently shown [6] that the restricted OBDD aj proof system, consisting only of the rather weak Axiom and Join rules which correspond to the Apply OBDD operator (i.e., disallowing symbolic quantifier elimination and reordering), does not polynomially simulate unrestricted resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a lot of interest in the relative efficiency of satisfiability checking methods based on resolution and OBDDs [1,2,3,4,5,6]. While OBBDs in general are known to be in cases exponentially more efficient that unrestricted resolution [7], it has been recently shown [6] that the restricted OBDD aj proof system, consisting only of the rather weak Axiom and Join rules which correspond to the Apply OBDD operator (i.e., disallowing symbolic quantifier elimination and reordering), does not polynomially simulate unrestricted resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Sinz and Biere [6] and later Biere [1] describe and discuss a system of proof traces and checking for Sat solvers based on conflict-driven clause learning, such as zchaff, minisat, picosat, and many others. In many respects, their proposal is simply the union of two earlier ground-breaking proposals: Goldberg and Novikov proposed to output the literals of each derived conflict clause [4], while Zhang and Malik proposed to output the sequence of clause numbers whose linear resolution would create each derived conflict clause [9].…”
Section: Introductionmentioning
confidence: 99%
“…We have instrumented two other already existing solvers, (i) the BDD-based solver Ebddres [29,30] and (ii) the search-based solver Quaffle [12]. Ebddres produces both models and refutation traces whereas with Quaffle we are so far limited to refutation traces.…”
Section: Methodsmentioning
confidence: 99%
“…Then the logical operations of the solving algorithm are traced until it is shown that the Tseitin variable for the constant BDD zero has to be true, a contradiction. All the details except for universal quantification can be found in [29,30]. For universal quantification, the proof rule is as follows.…”
Section: Methodsmentioning
confidence: 99%